HLA-E gene polymorphisms in chronic hepatitis C: Impact on HLA-E liver expression and disease severity - Araujo, Roberta Chaves; Bertol, Bruna Cristina; Dias, Fabricio Cesar; Debortoli, Guilherme; Almeida, Patricia Holanda; Souza, Fernanda Fernandes; Villanova, Marcia Guimaraes; Ramalho, Leandra Naira Zambelli; Martinelli, Ana Lourdes Candolo; Castelli, Erick da Cruz [UNESP]; Mendes Junior, Celso Teixeira; Donadi, Eduardo Antonio (Elsevier B.V., 2021)
Hepatitis C virus usually produces chronic infection and liver damage. Considering that: i) the human leukocyte antigen-E (HLA-E) molecule may modulate the immune response, and ii) little is known about the role of HLA-E gene variability on chronic hepatitis C, we studied the impact of HLA-E polymorphisms on the magnitude of HLA-E liver expression and severity of hepatitis C. HLA-E variability was evaluated in terms of: i) single nucleotide polymorphism (SNP) alleles and genotypes along the gene (beginning of the promoter region, coding region and 30UTR), and ii) ensemble of SNPs that defines the coding region alleles, considered individually or as genotypes. The comparisons of the HLA-E variation sites between patients and controls revealed no significant results. The HLA-E + 424 T > C (rs1059510), +756 G > A (rs1264457) and + 3777 G > A (rs1059655) variation sites and the HLA-E*01:01:01:01 and HLAE*01:03:02:01 alleles, considered at single or double doses, were associated with the magnitude of HLA-E liver expression in Kupfer cell, steatosis, inflammatory activity and liver fibrosis. Although these associations were lost after corrections for multiple comparisons, these variable sites may propitiate biological clues for the understanding of the mechanisms associated with hepatitis C severity. (C) 2021 American Society for Histocompatibility and Immunogenetics. Published by Elsevier Inc. All rights reserved.
Keywords: Chronic hepatitis C; HLA-E gene; HLA-E liver expression; Liver injury